Evaluación Agronómica del cultivo de maíz dulce (Zea mays) con aplicación de reguladores de crecimiento en estados fenológicos en la zona de Babahoyo - Olaya Méndez, Genesis Julisa (2023)
The cultivation of sweet corn is one of the most important on a global scale for many reasons, among the most relevant are nutrition, since it is considered one of the most basic foods. For this reason, in the present study, the use of different types of growth regulators was evaluated in a very important crop such as sweet corn. The different types of growth regulators that were used are Fruit-XL, X-Cyte and Cytochem in different doses. The experimental design was used complete randomized blocks with three repetitions, the evaluation of means was carried out with Andeva and the comparison of means with the 95% Tukey test. The data that were evaluated are plant height, insertion height, leaf area index, days to flowering, ear length, ear diameter, weight of ear with gopher, weight of shelled ear, shelling index, number of ears can, grain yield per hectare and economic analysis. As a result, it was obtained that the growth regulator with the highest performance in the production of the sweet corn crop was Fruit-XL at a dose of 0.35 l/ha since it achieved that the plants obtained a greater height, leaf area index, length of cob, cob diameter, cob weight with gopher, shelling index and grain yield per hectare.